Error Analysis on Essay Writing Organization - apandi apandi; wendi kusriandi (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2016)
This research is designed to analyze students’ error on essay writing organization. The writers focus on the one category of error identifications that is organization. By conducting this research, the writers hope some development of students’ ability in arranging essay. By analazing the erros, students get feed back to develop their ability. This study was conducted descriptively and qualitatively in nature. It is designed to identify and to describe kinds of errors is made by the student in essay writing organization in the EFL classroom. To achieve the goal, the writers describe in detail all the data taken from the students’ works and interpreted to make an empirical generalization. This research was conducted in second grade of English department in one of the university in Cirebon. The writers use purposive random sampling. The result of findings show that 16 students stand in scale 3 which is equal with 64 %. Then, 7 students stand in scale 4 which is equal with 28 %. And the last, 2 students stand in scale 2 which is equal with 8 %. So that, the writer concluded that the students of second grade of UNSWAGATI Cirebon are adequate to fair on essay writing organization.